Night shift - King, Stephen, 1947- (New York : Doubleday, 1978)
A collection of nineteen horror stories, including "Night Surf," "Sometimes They Come Back," "The Lawnmower Man," and "Children of the Corn.".
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Booklist, March 2002.
Notable/Best Books (A.L.A.), April 2002.
Wilson's Fiction, March 2006.
Keywords: Horror fiction; Short stories; Horror fiction; Short stories